Neural Correlates of Executive Functioning in Anorexia Nervosa and Obsessive–Compulsive Disorder - Thomas, Kai S.; Birch, Rosalind E.; Jones, Catherine R. G.; Vanderwert, Ross E. (Frontiers in Human Neuroscience, 2022)
Anorexia nervosa (AN) and obsessive-compulsive disorder (OCD) are commonly reported to co-occur and present with overlapping symptomatology. Executive functioning difficulties have been implicated in both mental health conditions. However, studies directly comparing these functions in AN and OCD are extremely limited. This review provides a synthesis of behavioral and neuroimaging research examining executive functioning in AN and OCD to bridge this gap in knowledge. We outline the similarities and differences in behavioral and neuroimaging findings between AN and OCD, focusing on set shifting, working memory, response inhibition, and response monitoring. This review aims to facilitate understanding of transdiagnostic correlates of executive functioning and highlights important considerations for future research. We also discuss the importance of examining both behavioral and neural markers when studying transdiagnostic correlates of executive functions.